THE CONTINUITY AND CHANGE OF DIYAT AS AN ALTERNATIVE TO ISLAMIC CRIMINAL SANCTIONS IN UNDHANG-UNDHANG BANTĚN DURING THE 17th – 18th CENTURIES - Muhammad Ishom (Islam Futura, 2023)
This research emphasizes the shift from the archaic trend of applying corporal punishment to other types of humane punishment in pre-modern periods. This phenomenon occurred not only in the Western world but also in the Eastern and Islamic worlds. One of them was the criminal law contained in the Banten Law (UUB), which was implemented in the Banten sultanate between the 18th and 19th centuries. Islamic criminal law in the form of qişaş and hudûd sanctions was no longer applied in Banten, but was replaced with more humane fines or diyat sanctions. Was the criminal law reform in the sultanate of Banten influenced by developments in Western law? One of the explanations given in the UUB was that the sultan of Banten employed the view of the Maliki school of thought, which allowed the ruler the right to impose takzir on criminal cases that had been resolved by Islamic law sanctions. The legal case for using diyať sanctions instead of qišaš and hudûd punishments was more substantial if takzir punishment was employed. This study used data in the form of UUB manuscript (single text) with the code number LOr 5598. The legal texts in UUB were analyzed using a legal social history approach. This study concludes that the application of law in UUB has dogmatic reasons for Islamic criminal law and the interests of siyasať syar'iyať.